The Relevance of the High Frequency Audiometry in Tinnitus Patients with Normal Hearing in Conventional Pure-Tone Audiometry. (25th October 2015) - Vielsmeier, Veronika; Lehner, Astrid; Strutz, Jürgen; Steffens, Thomas; Kreuzer, Peter M.; Schecklmann, Martin; Landgrebe, Michael; Langguth, Berthold; Kleinjung, Tobias
Abstract : Objective . The majority of tinnitus patients suffer from hearing loss. But a subgroup of tinnitus patients show normal hearing thresholds in the conventional pure-tone audiometry (125 Hz–8 kHz). Here we explored whether the results of the high frequency audiometry (>8 kHz) provide relevant additional information in tinnitus patients with normal conventional audiometry by comparing those with normal and pathological high frequency audiometry with respect to their demographic and clinical characteristics. Subjects and Methods . From the database of the Tinnitus Clinic at Regensburg we identified 75 patients with normal hearing thresholds in the conventional pure-tone audiometry. We contrasted these patients with normal and pathological high-frequency audiogram and compared them with respect to gender, age, tinnitus severity, pitch, laterality and duration, comorbid symptoms and triggers for tinnitus onset. Results . Patients with pathological high frequency audiometry were significantly older and had higher scores on the tinnitus questionnaires in comparison to patients with normal high frequency audiometry. Furthermore, there was an association of high frequency audiometry with the laterality of tinnitus. Conclusion . In tinnitus patients with normal pure-tone audiometry the high frequency audiometry provides useful additional information. The association between tinnitus laterality and asymmetry of the high frequency audiometry suggests a potential causal role for the high frequency hearing loss in tinnitus etiopathogenesis.